Formation and Dimensions of Marketing Culture under the Contemporary Conditions of Competition - Urbanskienė, Rūta; Žostautienė, Daiva (Ekonomika, 2002)
In order to survive in the market, companies seek competitive advantages. Unfortunately. under the contemporary conditions of competition, such conventional advantages, as lower price and better or more convenient packing of goods, are insufficient, as competitors may emulate these advantages rather quickly. New vantages that would be difficult to copy ould be judged by consumers as exclusive attributes of the activities of an enterprise are requisite. Such competitive exclusiveness in the market, and, particularly. in communication with consumers could be obtained with reference to marketing culture. The core of marketing culture will be revealed in this article through interface between the culture of an enterprise (organization) and marketing when answering the following questions: What is marketing culture? What are the main components and dimensions of marketing culture? What assumptions can be made about marketing culture for the company desiring to remain competitive?